A new magnetorheological elastomer isolator in shear–compression mixed mode. (July 2015) - Yang, CY; Fu, J; Yu, M; Zheng, X; Ju, BX
A new magnetorheological elastomer isolator in shear–compression mixed mode is designed in this article. Two pieces of magnetorheological elastomer fabricated with different dimensions are utilized in the isolator. One magnetorheological elastomer operates on shear mode, and the other operates on compression mode. Next, a finite element method magnetic package is used to analyze the designed magnetic circuit system, and a test system is established to obtain the frequency response of magnetorheological elastomer isolator with mixed mode. It is found that the natural frequency of magnetorheological elastomer isolator changes greatly with variable current applied, and the amplitude of vibration is attenuated widely. Compared with the natural frequency of 0 A, the increment of natural frequency is up to 103% with applied current reaches to 1.5 A. Finally, the dynamic model of isolator system is established, and the stiffness and damping coefficients of magnetorheological elastomer isolator are identified by the experimental method. Meanwhile, the variable range for stiffness and damping of magnetorheological elastomer isolator with mixed mode is greater than that of single mode, which has been proved in theory and experiments.